Job-Related and Nonjob-Related Gossips Among Low-Ranked Employees in Unionized Service Organization - Bashir, Mohsin; Shabbir, Rizwan; Saleem, Sharjeel; Abrar, Muhammad; Saqib, Shahnawaz; Gill, Shahzad Habib (Frontiers in Psychology, 2020)
Workplace incivility is a common phenomenon that is frequently found across all organizations and cultures. This study was planned to investigate the impact of workplace incivility on job and non-job related gossips through the mediating role of cynicism and psychological contract violation. The perspective of low-ranked unionized employees was explored through a survey method by using stratified sampling in eight strata, which were formulated based on geographical distribution. A total of four hundred questionnaires were distributed among the employees of eight circles, 50 from each, while use able responses remained 301. SmartPLS was used to analyze the data through structural equation modeling. From a theoretical perspective, this study has made several contributions by investigating the impact of workplace incivility in the South Asian context and documenting the impact of incivility from the perspective of individuals belonging to minority socio-cultural status. Besides supporting existing literature, this study provided a unique argument that low-ranked employees in South Asian societies do not spread nonjob-related gossips. This finding is contradictory to the existing literature; and, thus, calls for future research to identify this inconsistency. Limitations and future directions are also discussed.